2017
DOI: 10.1080/14764172.2017.1303170
|View full text |Cite
|
Sign up to set email alerts
|

Punch graft versus follicular hair transplantation in the treatment of stable vitiligo

Abstract: Punch grafting is more effective than follicular grafting in the treatment of stable vitiligo; however, follicular hair transplantation is cosmetically better, so we recommend it in exposed areas as face.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…35 The most common adverse effect after PG was a cobblestone appearance, reported in up to 90% of patients. 33 Dyspigmentation (hypo-, hyper-, or depigmentation) was reported occasionally at the donor site.…”
Section: Resultsmentioning
confidence: 99%
“…35 The most common adverse effect after PG was a cobblestone appearance, reported in up to 90% of patients. 33 Dyspigmentation (hypo-, hyper-, or depigmentation) was reported occasionally at the donor site.…”
Section: Resultsmentioning
confidence: 99%
“…al., 2014, 16 while Mohamed et. al., 2017, 17 used strip technique for FUT and punches of 2 mm size for mPG.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning type of vitiligo, a statistically significant relation between segmental vitiligo and the response to treatment was present. Previous studies did not mention the relation between response to treatment by FUT and type of vitiligo 1,11,16,17 …”
Section: Discussionmentioning
confidence: 99%
“…reported that in the recipient site, cobblestone appearance was the predominant complication in mini punch grafts, whereas hyperpigmentation and thickening of grafts were common in suction blister roof grafts. Mohamed et al 20 . compared mini punch grafts and hair follicle graphs in the treatment of 32 patients with stable vitiligo, and found that the improvement of vitiligo in patients who underwent mini punch graft treatment was significantly higher than that of patients who underwent follicular hair grafts.…”
Section: Surgical Treatmentmentioning
confidence: 99%